Persiapan Menuju Indonesia Emas 2045: Analisis Efektifitas Program MBG dan Peningkatan Status Gizi Anak Sekolah - Salsabila Ayu Arifia; Fariska Wahyuni; Zef Risal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Indonesia Emas 2045 is a vision that calls for the creation of a superior generation through improved health and education. One of the main challenges in achieving this vision is addressing nutritional issues, particularly among school-age children. This study aims to analyze the effectiveness of the Free Nutritious Meal Program (MBG) in improving the nutritional status of schoolchildren in Indonesia. This study used a literature review approach by identifying, assessing, and evaluating research publications from 2020-2025. The results indicate that the implementation of the MBG has the potential to improve the nutritional status of schoolchildren, contribute to reducing stunting rates, and support the achievement of a higher Human Development Index (HDI). However, the MBG program faces several challenges in its implementation, including logistics, funding sustainability, and menu suitability for local nutritional needs in various regions. These challenges need to be addressed to maximize the program's impact. It can be concluded that the success of the MBG program significantly impacts the achievement of the Indonesia Emas 2045 vision, with the younger generation being key to increasing the nation's competitiveness and productivity.